Killer visual strategies : engage any audience, improve comprehension, and get amazing results using visual communication - Balliett, Amy (John Wiley & Sons, Inc., 2020)
"Over the past decade, visual communication has shifted from being an optional medium for transmitting information to an essential means of build connection and understanding. It has changed the way we tell stories and establish relationships -- and it has transformed the traditional agency model within the marketing, public relations, and design industries. Amy Balliett's book will explain how can marketers, PR professionals, and organizations can connect and thrive in a world that demands quality visual content"--